Physics around us : how and why things work - Henley, Ernest M.; Dash, J. Gregory (New Jersey: World Scientific, 2012)
This book is suitable for a first year, non-calculus physics course. It covers mechanics, fluids, gravitation, thermal physics, electricity and magnetism, and modern physics, including atoms, an introduction to quantum mechanics, special relativity, and nuclear and particle physics. Trigonometric functions and vectors are introduced as needed.
Index of famous scientists 355-356p.; Subject index 357-361p.
Keywords: Electricity and magnetism; Mechanics; Modern physics; Physics